Stability of the hcp Ruthenium at high pressures from first principles - Lugovskoy, Andrey; Belov, M.; Krasilnikov, O.; Vekilov, Y. (American Institute of Physics Inc., 2014)
The method of calculation of the elastic constants up to third order from the energy-strain relation under pressure for the hcp crystals is given and described in details. The method is applied to the hcp phase of Ruthenium. Elastic constants, lattice dynamics, and electronic structure are investigated in the pressure interval of 0-600 GPa by means of first principles calculations. The obtained parameters are in very good agreement with available experimental and theoretical data. No preconditions for phase transformation driven by mechanical or dynamical instabilities for hcp Ru were found in the investigated pressure range. The reason of stability at such high pressures is explained in the context of electronic structure peculiarities.